2020
DOI: 10.1088/2515-7647/ab83e3
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping and orientation-resolved spectroscopy of europium-doped nanorods

Abstract: Europium-doped NaYF 4 nanorods with a high aspect ratio are optically trapped using a single fibre tip optical tweezers. Three distinct trapping positions of the nanorods are observed: in contact with the fibre tip, close to the tip and 5 µm from the tip end. The direction and polarisation-dependent Eu 3 + photoluminescence is investigated by recording the emission parallel and perpendicular to the nanorod long axis through the trapping fibre and the microscope objective, respectively. These spectroscopic meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The implementation of a flexibly controlled system of optical tweezers using optical fibers is described in a number of reviews [120,150,151] and original papers [152]. Combining waveguides with evanescent-wave and plasmon-polariton optics [153] based on nanostructured resonators opens up a number of promising solutions for creating tools for noninvasive manipulation of nanostructures [154,155], individual cell organelles, in particular, DNA nucleotides, whose dimensions are units and tens of nanometers [156].…”
Section: Single-beam Trapsmentioning
confidence: 99%
“…The implementation of a flexibly controlled system of optical tweezers using optical fibers is described in a number of reviews [120,150,151] and original papers [152]. Combining waveguides with evanescent-wave and plasmon-polariton optics [153] based on nanostructured resonators opens up a number of promising solutions for creating tools for noninvasive manipulation of nanostructures [154,155], individual cell organelles, in particular, DNA nucleotides, whose dimensions are units and tens of nanometers [156].…”
Section: Single-beam Trapsmentioning
confidence: 99%
“…For example, Leménager et al ( 2018 ) recorded the anisotropic emission of trapped NaYF 4 :Er,Yb,Gd nanorods in three orthogonal directions using distinct methods: through the microscope objective, by coupling it into one of the trapping fiber tip, and by coupling it into a third fiber (see Figures 1E,F ). In a similar way, Kumar et al ( 2020 ) studied nanorods of NaYF 4 :Eu, measuring their 3D orientation by europium ion polarization-dependent luminescence.…”
Section: Optical Trapping Of Lanthanide-doped Nanoparticlesmentioning
confidence: 99%
“…Such material effects are especially interesting in micro- and nanoscale single crystals in which the light polarization, the crystal orientation, and the lattice symmetry are closed linked. Indeed, it is well observed that the aligned assembly of microcrystals emits light of partially linear polarization while the emission from randomly oriented assemble remains unpolarized. The partially polarized emission was further confirmed by the accurate micro-photoluminescence (μ-PL) measurements on single microcrystals in both real and angular spaces, and a technology was recently developed to obtain the information on the three-dimensional (3D) orientation of a single microcrystal by just measuring the relative intensities of the polarization emissions toward the collecting lens . With these advantageous properties, the micro- and nanocrystals can serve as powerful sensors for the single-particle tracking, supercrystallographic reconstruction, and indirect measurement of the local shear rate in microfluids .…”
Section: Introductionmentioning
confidence: 99%